CD34 and Wnt3 expression in potentially malignant oral disorders - Nader, Noroz Hama Rashid; Al Hmedat, Ibrahim Gataa Gataa; Mohammad, Dena Nadhim; Garib, Balkees Taha (Journal of Baghdad College of Dentistry, 2017)
Background: Potentially malignant oral disorders (PMODs) are common precursors of oral squamous cell carcinoma (OSCC). Neoangiogenesis and signalling are important intermediate biomarkers that may govern the progression of dysplastic mucosa into carcinoma. Aims: Evaluate the importance of CD34 and Wnt3 expression in PMODs and OSCCs in relation to their clinicopathological parameters. Settings and Design: Prospective cross-sectional study. Materials and Methods: Immunohistochemical staining for CD34 and Wnt3 was performed for 41 samples. These included 27 PMODs, six OSCCs and eight normal gingival and alveolar mucosa. Analysis of variance (ANOVA) and post-hoc tests were applied. P